Humoral Autoimmune Responses to Insulin-Like Growth Factor II mRNA-Binding Proteins IMP1 and p62/IMP2 in Ovarian Cancer. (27th April 2014) - Liu, Xinxin; Ye, Hua; Li, Liuxia; Li, Wenjie; Zhang, Yi; Zhang, Jian-Ying
Abstract : Ovarian cancer is one of the leading causes of cancer-related deaths among women. There is an urgent need of better approaches for the identification of appropriate biomarkers in the early detection of ovarian cancer. The aim of this study was to elucidate the significance of autoantibodies against insulin-like growth factor II mRNA-binding proteins (IMPs) in patients with ovarian cancer. In this study, autoantibody responses to two members (IMP1 and p62/IMP2) of IMPs were evaluated by enzyme-linked immunosorbent assay (ELISA), western blotting, and indirect immunofluorescence assay in sera from patients with ovarian cancer and normal human individuals. The results have demonstrated that both IMP1 and p62/IMP2 can induce relatively higher frequency of autoantibody responses in patients with ovarian cancer (26.5% and 29.4%) compared to normal individuals ( P < 0.01 ) . Our preliminary data suggest that IMP1 and p62/IMP2 can stimulate autoimmune responses in ovarian cancer, and anti-IMP1 and anti-p62/IMP2 autoantibodies could be used as potential biomarkers in immunodiagnosis of ovarian cancer.